2014
DOI: 10.2147/ott.s58622
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin: a key player in cancer chemoresistance and its inhibition

Abstract: Clusterin is a heterodimeric disulfide-linked glycoprotein (449 amino acids) isolated in the rat prostate after castration. It is widely distributed in different tissues and highly conserved in species. There are two isoforms (1 and 2) with antagonistic actions regarding apoptosis. Clusterin is implicated in a number of biological processes, including lipid transport, membrane recycling, cell adhesion, programmed cell death, and complement cascade, representing a truly multifunctional protein. Isoform 2 is ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 65 publications
3
111
1
1
Order By: Relevance
“…We identified a total of 399 proteins, mostly related to adhesion and the cytoskeleton (Supplementary Table S4), indicating that there were microvesicle-like exosomes in the NCI-H2052 supernatant. Among the 399 supernatant proteins, interleukin-8 (IL-8), 16 growth-regulated α-protein (GROα), 16 midkine (MK), 17 IL-18, 18 IL-6, 19 hepatoma-derived growth factor (HDGF), 20 clusterin (CLU) 21 and granulin (GRN) 22 are known to be involved in tumor angiogenesis. We examined the involvement of IL-8, GROα, IL-18 and IL-6 in tube formation induced by the NCI-H2052 supernatant using commercially available neutralizing antibodies corresponding to each of the above proteins or protein receptors.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a total of 399 proteins, mostly related to adhesion and the cytoskeleton (Supplementary Table S4), indicating that there were microvesicle-like exosomes in the NCI-H2052 supernatant. Among the 399 supernatant proteins, interleukin-8 (IL-8), 16 growth-regulated α-protein (GROα), 16 midkine (MK), 17 IL-18, 18 IL-6, 19 hepatoma-derived growth factor (HDGF), 20 clusterin (CLU) 21 and granulin (GRN) 22 are known to be involved in tumor angiogenesis. We examined the involvement of IL-8, GROα, IL-18 and IL-6 in tube formation induced by the NCI-H2052 supernatant using commercially available neutralizing antibodies corresponding to each of the above proteins or protein receptors.…”
Section: Resultsmentioning
confidence: 99%
“…This multifunctional protein is associated with clearance of cellular debris and apoptosis, as well as with lipid transport, membrane recycling, cell adhesion, tumor progression, and neurodegenerative disorders. 32 Clusterin is known to be expressed in the ocular surface epithelium, but it is significantly reduced in the keratinized conjunctiva, suggesting its potential role in maintaining the ocular surface epithelium in a non-keratinizing state. 33,34 In addition, it has been found that Clusterin strongly binds MMP-9, inhibiting its enzymatic activity and MMP-9-mediated degradation of the tight junction structures formed between human epithelial cells, thereby preventing tumor invasion.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, they have distinct biological functions, e.g. sCLU reportedly can prevent cell death while nuclear can promote cell death (Kim et al 2012;Koltai 2014). To clarify the function of sCLU, we utilized intraventricular infusion of exogenous human ApoJ protein following CCI in mice.…”
Section: Discussionmentioning
confidence: 99%